Sedimentary facies control on sandstone reservoir properties: A case study from the permian Shanxi Formation in the southern Ordos basin, central China. (July 2021) - Li, Yang; Fan, Aiping; Yang, Renchao; Sun, Yipu; Lenhardt, Nils
Abstract: During the Upper Paleozoic large-scale tight sandstone oil and gas reservoirs developed in the southern Ordos Basin of China. Due to the heterogeneity of sedimentary facies and diagenesis, the reservoir quality of these deposits is extremely uneven. Based on field profile observations, conventional thin section, cast thin section and scanning electron microscope (SEM) analysis, combined with general physical analysis, the sedimentary characteristics, physical properties and main controlling factors of the reservoirs of the Upper Paleozoic Shanxi Formation of the southern Ordos Basin were determined. The results of this contribution show that the Shanxi Formation is dominated by delta facies, with small-scale lacustrine facies. The delta facies can be further divided into distributary channel, natural levee, interdistributary swamp, underwater distributary channel, underwater distributary bay, mouth bar and sand sheet microfacies. Diagenesis within the study area has generally entered the mesodiagenetic B phase. Compaction and cementation were the main destructive stages of diagenesis. While cementation blocked the reservoir pores and reduced the physical properties, dissolution effectively improved the physical properties of the reservoir. The physical reservoir properties of the studied sandstone reservoirs are controlled by different sedimentary microfacies that are mainly, represented by distributary channel, underwater distributary channel and mouth bar microfacies that also show the best properties. These microfacies are followed by sand sheets. The lowest properties can be observed in the natural levees. Graphical abstract: Image 1 Highlights: The Permian Shanxi Formation is dominated by delta facies, with subordinate, small-scale lacustrine facies. Reservoir properties are mainly controlled by sedimentary microfacies. Compaction and cementation are the main processes for destruction of primary porosity. Dissolution of feldspars and lithic particles is the main process for increase in porosity and permeability.